A Novel Validated Recurrence Risk Score to Guide a Pragmatic Surveillance Strategy After Resection of Pancreatic Neuroendocrine Tumors: An International Study of 1006 Patients. Issue 3 (September 2019) - Zaidi, Mohammad Y.; Lopez-Aguiar, Alexandra G.; Switchenko, Jeffrey M.; Lipscomb, Joseph; Andreasi, Valentina; Partelli, Stefano; Gamboa, Adriana C.; Lee, Rachel M.; Poultsides, George A.; Dillhoff, Mary; Rocha, Flavio G.; Idrees, Kamran; et al.
Abstract : Objective: Despite heterogeneous biology, similar surveillance schemas are utilized after resection of all pancreatic neuroendocrine tumors (PanNETs). Given concerns regarding excess radiation exposure and financial burden, our aim was to develop a prognostic score for disease recurrence to guide individually tailored surveillance strategies. Methods: All patients with primary nonfunctioning, nonmetastatic well/moderately differentiated PanNETs who underwent curative-intent resection at 9-institutions from 2000 to 2016 were included (n = 1006). A Recurrence Risk Score (RRS) was developed from a randomly selected derivation cohort comprised of 67% of patients and verified on the validation-cohort comprised of the remaining 33%. Results: On multivariable analysis, patients within the derivation cohort (n = 681) with symptomatic tumors (jaundice, pain, bleeding), tumors >2 cm, Ki67 >3%, and lymph node (LN) (+) disease had increased recurrence. Each factor was assigned a score based on their weighted odds ratio that formed a RRS of 0 to 10: symptomatic = 1, tumor >2 cm = 2, Ki67 3% to 20% = 1, Ki67 >20% = 6, LN (+) = 1. Patients were grouped into low- (RRS = 0–2; n = 247), intermediate-(RRS = 3–5; n = 204), or high (RRS = 6–10; n = 9)-risk groups. At 24 months, 33% of high RRS recurred, whereas only 2% of low and 14% of intermediate RRS recurred. This persisted in the validation cohort (n = 325). Conclusions: This international, novel, internally validated RRS accurately stratifies recurrence-free survival for patients with resected PanNETs. Given their unique recurrence patterns, surveillance intervals of 12, 6, and 3 months are proposed for low, intermediate, and high RRS patients, respectively, to minimize radiation exposure and optimize cost/resource utilization.